Developing Water Leaders as Catalysts for Change: The Nebraska Water Leaders Academy. (2nd September 2019) - Burbach, Mark E.; Reimers‐Hild, Connie
Abstract: Managing water resources is increasingly complex and dynamic. Sustaining freshwater ecosystem services in the face of increasing challenges and emerging threats is a supreme leadership challenge. Leadership development program designers should look to social science theories and methods to prepare leaders to catalyze the change necessary to meet future challenges. This paper provides evidence that a new generation of water leaders is needed; and correspondingly, there is a need for new leadership development programs. The Nebraska Water Leaders Academy and its evaluation is presented as a case study of a successful program training leaders in social science‐based skills in order to produce catalysts of change. The Academy is theoretically grounded in transformational leadership, champions of innovation, civic capacity, and entrepreneurial leadership. The Academy employs a process‐based curriculum with developmental experiences that includes key components of assessment, challenge, and support. Formative assessment provides constructive feedback from participants and guides the development of future sessions and curriculum. Summative assessment is used to gauge participants' leadership knowledge, skills, and behaviors, and evaluate the instructional methods used in the Academy. Results of pre‐ and post‐Academy assessments of participants from both the participants' and raters' perspectives indicate statistically significant increases in transformational leadership behaviors, champion of innovation behaviors, civic capacity, entrepreneurial leadership behavior, awareness of Nebraska water issues, and engagement with Nebraska water issues.